Microsoft Identity and Access Administrator Associate (SC-300) Cert Prep by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2024)
Microsoft MVP Tim Warner shares tips to help you prepare for the Microsoft SC-300 certification exam.